Students’ Foreign Anxiety Reviewed from Religiosity through the Mediation of Learning Motivation - Nashori, Fuad; Hidayat, Bahril; Anshori, Adam; Putra, Ary Antony; Suroso, Rasyid Fahmi; Novariana, Noor Winda (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this study is to understand the role of religiosity towards anxiety in using English language through learning motivation mediators. In this research, four questionnaires were used, namely the foreign languages classroom anxiety scale, religiosity scale, the test of religious knowledge, and learning motivation scale. The subjects involved were 202 students. The regression analysis techniques on the data shows that (1) Religiosity is a predictor of learning motivation (2) Learning motivation as a predictor of Foreign Language Anxiety, (3) Religiosity is not a direct predictor of Foreign Language Anxiety, and (4) Learning motivation perfectly mediates the relationship between religiosity and Foreign Language Anxiety.